Isolation methods and culture conditions of human umbilical vein endothelial cells from Malaysian women - Raja Nor Suhaila,; Sabreena Safuan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Human umbilical vein endothelial cell (HUVEC) isolated from umbilical cord is widely used as endothelial cell model. However, HUVEC has been characteristically hard to maintain and showed molecular heterogeneity depending on the umbilical cord donors. Commercial HUVEC is commonly derived from European and Caucasian population which have different molecular characteristics from Asian women. This study aimed to optimize the isolation and culture condition of HUVEC using combinations of growth factors and extracellular matrix components so that the isolated HUVEC will purely represent the population under study. Umbilical cords were obtained from women post-labour. Different incubation times and digestive enzymes were used during endothelial cells isolation process. The culture conditions were optimized based on the coating materials and the media supplements. The results showed that 0.1% collagenase for 40 min incubation was the optimal isolation condition of HUVEC. HUVEC grown in 0.2% gelatin coated plate with 10% heat-inactivated fetal calf serum showed higher proliferative capacity and reduced cell death compared to other conditions (p<0.05). The results generated from this study provide a basic protocol of HUVEC isolation and culture conditions in order to generate working endothelial cell populations purely represent the Malaysian population.